(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Bacteriocins is a natural preservative (bio-preservatives) that can safely be used for food. Bacteriocins can be produced by a group of Lactic Acid Bacteria (LAB). Several strains of lactic acid bacteria (LAB) is bactericidal against gram positive and gram negative bacteria. The purpose of this study was to analyze the bacteriocins produced by Lactobacillus plantarum in chicken meat and determine the level of the last and long-term. Factors that are seen in this study is the levels of bacteriocins and also the duration of storage of chicken meat. The levels of bacteriocins is 0% and 10% by way of spraying in chicken meat and duration of storage are at 0, 5, 10, 15, 20, and 25 hours at room temperature. This study used a factorial completely randomized design with three replications. Plantaricin concentration against pH and aw values were significantly different (P<0.05). The test result of storage duration against water content were significantly different (P<0.05). Treatment of plantarisin IIA-1A5 10% to maintain the condition of chicken meat was better than treatment without the adding plantarisin.